VALUE BASED DECISION ON TECHNOLOGY CRITERIA THAT ARE RESILENT AGAINST GLOBAL ECONOMIC UNCERTAINTY - Genta Bintang Al Akbar; Raflis; Giraldi Fardiaz Kuswanda (International Journal on Livable Space, 2021)
Infrastructure development is important in today's society. This has become an obstacle with the increasing number of residents in DKI Jakarta, because land is limited and has not been proportional to population growth. The COVID-19 pandemic has gradually paralyzed the world economic system. Currently, Indonesia is on the brink of recession. The IMF estimates that the global economy will experience a decline in growth rates of up to -3%. To determine the impact of global economic uncertainty on construction projects, the most appropriate alternative standards and strategies are needed from the criteria for technologies that are resilient to global economic uncertainty. In this research, there are 5 criteria and 3 alternatives that underlie the goal of the best strategy in the aspect of technology for Value Based Decision Making against global economic uncertainty. AHP is used to examine the importance level data by asking for opinions from 10 experts for criteria and alternatives. Based on the results of distributing questionnaires to experts, it is known that Office Building Construction is an alternative and Building Materials criteria are the most suitable criteria against economic uncertainty.